Description The Knowledge And Willingness To Participate In The Covid-19 Vaccination In The Luwu Community - Hiyara, Miftahul; Pakadang, Sesilia Rante; Adhayanti, Ida (Universitas Dehasen Bengkulu, 2024)
At the end of 2019 a pandemic emerged from China in the city of Wuhan known as covid-19 which is a viral infectious disease caused by SARS-CoV (Severe Acute Respiratory Syndrome Corona Virus) which attacks the respiratory tract, this virus can spread quickly . Seeing a situation like this, the government has taken a policy by implementing social distancing recommendations and developing vaccines to prevent the wider spread of this pandemic. The purpose of this study was to describe the knowledge and willingness to participate in the covid-19 vaccination in the Luwu community. By using a descriptive survey method, sampling using a purposive sampling method with a total sample of 100 respondents. The results showed that the level of knowledge of the respondents 80% were in the very good category, 18% in the good category and a small part were in the fairly good category, namely 2%. And the level of willingness of most of the respondents are in the willing category as much as 50%. 48% are very willing and a small part are in the moderately willing category, namely as much as 2%. So from the results of this study it can be concluded that the picture of community knowledge is in the very good category (92%) and the picture of willingness is in the very willing category (78.8%).